Molecular design of thermally activated delayed fluorescent emitters for narrowband orange–red OLEDs boosted by a cyano-functionalization strategy. Issue 27 (17th June 2021) - Liu, Yang; Xiao, Xin; Ran, You; Bin, Zhengyang; You, Jingsong
Abstract : The first example of narrowband orange–red MR-TADF emitters has been developed, which realizes a record-high EQE of 33.7% in OLEDs. Abstract : The establishment of a simple molecular design strategy to realize red-shifted emission while maintaining good color purity for multi-resonance induced thermally activated delayed fluorescent (MR-TADF) materials remains an appealing yet challenging task. Herein, we demonstrate that the attachment of a cyano (CN) functionality at the lowest unoccupied molecular orbital location of the MR-TADF skeleton can promote attractive red-shifted emission due to the exceptional electron-withdrawing capacity of the CN group, which represents the first example of orange–red MR-TADF emitters. Meanwhile, the linear CN group adopts a coplanar conformation with the MR-framework to restrict structure relaxation associated with rotation, which is beneficial to maintain a small full-width at half-maximum and thus a good color purity. The CNCz-BNCz -based OLED device, which utilizes a TADF sensitized mechanism to accelerate the up-conversion process of triplet excitons in the emitting layer, exhibits an outstanding external quantum efficiency (EQE) as high as 33.7%, representing the state-of-the-art performance for orange–red TADF-OLEDs.